Artificial Regeneration of Sal and Teak - Ganguly, J. K. (Indian Forester, 1963)
The artificial regeneration of sal and teak in the deciduous derelict sal forests of the laterite zone has proved successful. At the beginning, sal seeds were sown in trenches with the outbreak of monsoon. In clayey soil, the results were not satisfactory because of water-logging of trenches whereas in the drier areas having soil mixed with murram the moisture condition was too low for the survival of plants. So, from 1957, transplanting of sal in leaf cups was introduced with 80 to 100% success. The normal sowing followed by transplanting will ensure complete success. Teak was planted in 1’ Ã— 1’ pits filled up with prepared soil with subsequent manuring. The first growth was remarkable in some places attaining an average height of 4 feet. Further study to determine the limits of murram and sand deposits to which one can go for growing teak with success, has to be continued. The tract covered by the regulation methods described are the lateritic districts of Midnapore, Bankura, Burdwan, Birbhum and Purulia which represent the dry zone of West Bengal.